Rencana Strategis Perpustakaan Sekolah : Pendekatan Praktis - Komarudin Komarudin (Pustakaloka, 2011)
Environment always changes. It must be anticipated bythinking strategically, that is a rethinking of the organization,itsvision for the future. To achieve that visionrequires a mission. It also requires reexamining the organization’s strengths and weaknesses. Organization has to identify threats as well as opportunities that exist to encourage future directions. This article explains strategic planning practically especially that is implemented at school library.